DISCLOSURE OF AUTHORITY OF THE CORRUPTION ERADICATION COMMISSION (KPK) IN THE POST LAW CHANGE CORRUPTION ERADICATION COMMISSION - Ricky Pratama Ginting; Sumarno (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
After the passing of the Corruption Eradication Commission (KPK) Law, the position of the KPK, which was originally a non-governmental institution, is now included in the branch of government power (Auxiliary State Organ). The only corruption eradication institution (excluding the Police and Prosecutor's Office) that still survives to this day is the Corruption Eradication Commission, namely the independent commission which is given pro justitia authority in carrying out criminal acts of corruption. So far this has not been without criticism. In carrying out its duties and functions (before the revision of the Law), many experts criticized the institution for its "independent" status. The purpose of writing this journal is to find out whether changes to the Corruption Eradication Commission Law have given birth to the concept of an independent state institution for the Corruption Eradication Commission. This research uses normative legal research methods. Meanwhile, the approach taken uses a statutory approach and a conceptual approach. The results of this research explain that overall the changes to the Corruption Eradication Commission Law have not yet given rise to the concept of an independent state institution because there are still provisions in articles interfering with the independence of the Corruption Eradication Authority by the Corruption Eradication Commission.